CO2 capture efficiency and heat duty of solid acid catalyst-aided CO2 desorption using blends of primary-tertiary amines. (February 2018) - Srisang, Wayuta; Pouryousefi, Fatemeh; Osei, Priscilla Anima; Decardi-Nelson, Benjamin; Akachuku, Ananda; Tontiwachwuthikul, Paitoon; Idem, Raphael
Highlights: Solid acid catalysts (HZSM-5, γ-Al2 O3 ) promote CO2 desorption from blended amines. The experiments were performed in a bench scale full-cycle CO2 capture pilot plant. Effects of solid acid catalysts on absorption efficiency and heat duty were studied. 5 M MEA:1.25 M DEAB with HZSM-5 showed the best absorber efficiency and heat duty. Abstract: This study evaluated improvements in the CO2 capture process in terms of cyclic capacity, absorption efficiency and heat duty caused by using a primary amine (5 M MEA) blended with a tertiary amine (2 M MDEA or 1.25 M DEAB) and a catalyst-aided desorber loaded with two different solid acid catalysts (γ-Al2 O3 or HZSM-5) in a bench scale full cycle CO2 capture plant. The absorber and desorber were stainless steel pipes with inside diameter of 0.05 m and height of 1.50 m. The desorber was loaded with varying amounts of solid acid catalyst at an average bed temperature of 85 °C. The two mixed amine solvents tested, were compared with 5 M MEA each with a circulation rate of 0.06 L/min. Simulated flue gas, 15% CO2 in N2, was used at a total flow rate of 15 SLPM. The results showed that in 5 M MEA system, cyclic capacity and absorption efficiency increased while heat duty decreased when the catalyst amount was increased. In the case of mixed primary and tertiary amines, catalysts contribute to slight improvements. The increase in absorption efficiency was found to be in the order of 5 M MEA: γ-Al2 O3  < 5 M MEA: HZSM–5 < 5 M MEA: 2 M MDEA: γ-Al2 O3  < 5 M MEA: 2 M MDEA: HZSM–5 < 5 M MEA: 1.25 M DEAB: γ-Al2 O3  < 5 M MEA: 1.25 M DEAB: HZSM-5. The relative reduction in heat duty of the system was found to be in the order of 5 M MEA: 1.25 M DEAB: HZSM–5 < 5 M MEA: 2 M MDEA: HZSM–5 < 5 M MEA: 1.25 M DEAB: γ-Al2 O3  < 5 M MEA: 2 M MDEA: γ-Al2 O3  < 5 M MEA: HZSM-5 < 5 M MEA: γ-Al2 O3 .